Unveiling the omicron B.1.1. 529: The variant of concern that is rattling the globe - Dhar, Ruby; Talukdar, Joyeeta; Nayek, Arnab; Ajmeriya , Swati; Kumar, Arun; Karmakar, Subhradip (Asian Journal of Medical Sciences, 2022)
Most viruses–including SARS-CoV-2, seem to have evolved over time. The lack of stringent proofreading mechanisms makes viral DNA/RNA replication error-prone. When a virus replicates, it sometimes changes a little bit, which is called mutations. Any virus with one or more new mutations can be referred to as a “variant” of the original virus. The last 2 years have witnessed the emergence of a large number of variants. Since the pandemic’s beginning, the SARS-CoV-2 coronavirus has mutated extensively, resulting in the emergence of different variants of the virus. One of these is the delta variant (arising from Pango lineage B.1.617.2) that took the word in a storm this year (February-July). The current a variant of concern is the B.1.1.529 (Omicron) variant reported first from South Africa on November 24, 2021. In recent weeks, infections have been widely reported, along with the increased detection of the B.1.1.529 variant. We reviewed the emergence of the new variant (B1.1.529) and its possible outcomes.